The planter's prospect : privilege and slavery in plantation paintings. - Vlach, John Michael 1948- (The Richard Hampton Jenrette series in architecture and the decorative arts, 2002)
The Planter's Prospect is an illustrated exploration of the statements of power and ironic invasions encoded in plantation paintings created from the 19th century to the early 20th century. It focuses on oil paintings.